MicroRNAs in Liver Health and Disease - Hsu, Shu-hao (2013)
MicroRNAs (miRNAs), a class of short non-coding RNAs, have been studied intensely and extensively in the past decade in every aspect of biological processes, including cell differentiation, proliferation and death. These findings pointed out the pivotal role of miRNA in posttranscriptional control of gene expression in animals and established miRNAs as therapeutic targets for different pathophysiological processes, including liver disease. Here we have discussed the recent advances made in identifying the miRNAs deregulated in different liver diseases such as obesity, hepatitis, alcoholic and nonalcoholic steatohepatitis, cirrhosis and hepatocellular carcinoma, as well as pathophysiological conditions such as developmental abnormality. We have specifically reviewed the role of miRNAs in these diseases and discussed critically potential impacts of these miRNAs as biomarkers and/or therapeutic targets in liver pathobiology in the clinical setting. Finally, we have highlighted the latest techniques or preclinical and/or clinical trials that are being developed to replenish or inhibit the deregulated miRNAs.